Interval type-2 fuzzy sets based multi-criteria decision-making model for offshore wind farm development in Ireland. (1st May 2020) - Deveci, Muhammet; Cali, Umit; Kucuksari, Sadik; Erdogan, Nuh
Abstract: Offshore wind energy takes up an important place in Ireland's renewable generation portfolio thanks to its abundant offshore wind resource. Optimal offshore site selection and developing site-specific energy policy instruments are of key importance to the success of offshore wind energy investments. In this respect, this study aims at developing a multi-criteria decision-making (MCDM) model considering technical, economic, environmental and social criteria to assess Ireland's most promising offshore wind sites in terms of their sustainable development. An interval type-2 fuzzy sets based MCDM model is developed that integrates the score function with positive and negative solutions to achieve better results. Moreover, advanced energy economic metrics such as levelized cost of electricity with higher resolution are integrated into the decision-making process to make more precise decisions. Case studies are conducted for the five of the offshore sites in development pipeline. Results are compared to those of other state-of-the-art MCDM methods. It is found that Arklow Bank-2 is the most favorable site while Sceirde is the least site. The ranking of other sites is found to be Oriel > Dublin Array > Codling Park. It is shown that the proposed approach is superior in terms of stability and implementation as compared to its counterparts.